MIPAS measurements of upper tropospheric C2H6 and O3 during the Southern hemispheric biomass burning season in 2003 - (:unkn) unknown (My University, 2007)
Under cloud free conditions, the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) provides measurements of spectrally resolved limb radiances down to the upper troposphere. These are used to infer global distributions of mixing ratios of atmospheric constituents in the upper troposphere and the stratosphere. From 21 October to 14 November 2003, MIPAS observed enhanced amounts of upper tropospheric C2H6 (up to about 400 pptv, depending on spectroscopic data chosen) and ozone (up to about 80 ppbv). By means of trajectory calculations, the enhancements observed in the Southern hemisphere are, at least partly, attributed to a biomass burning plume, which covers wide parts of the Southern hemisphere, from South America, the Atlantic ocean, Africa, the Indian Ocean to Australia. The chemical composition of the part of the plume-like pollution belt associated with South American rainforest burning appears different from the part associated with Southern African savanna burning. In particular, African savanna fires lead to a larger ozone enhancement than South American rainforest fires.
Keywords: African Research